KUALITAS PELAYANAN PUBLIK PEMBUATAN KARTU TANDA PENDUDUK (KTP) DAN KARTU KELUARGA (KK) DI KANTOR KECAMATAN GONDANGREJO KABUPATEN KARANGANYAR - Jimin - (JI@P, 2015)
This study aimed to describe the quality of public services of RecidentialIdentity Card (Kartu Tanda Penduduk - KTP) and Family Identity Card(Kartu Keluarga - KK). Research was conducted at the Sub-District Office ofGondangrejo Karanganyar Regency. In order to measure the quality ofpublic services of those two cards, theory of service standard of Mahmudiwas exercised. The method used is descriptive qualitative. Data wascollected using interview and documentation collecting techniques.Sampling method of this study was purposive sampling employing snowballand accidental samplings methods. Informants in this study were the StaffHead of KTP public service and of KK and the costumers applying to haveKTP and KK. To validate the findings, data triangulation was employed.Interactive analysis model as suggested by Miles and Huberman wasmanipulated in this research. Based on research finding, it is concluded thatthe quality of public service of KTP card and of KK card, when it ismeasured from the aspect of procedures, it was found that fhe applicantsdid not face complex and complicated procedures. They were just requiredto have a letter of introduction issued by village head and a copy of the KKcard. Interms of time-needed, the completion needs short time because theprocessing of KTP and KK cards are supported by adequate computerequipment, thus inefficient matter of time before the service process can befinished optimally. Interms of cost of public services, it is found that the costof KTP and KK are free of charge. Research result also indicated that theproduct of KTP and KK cards are found good in which almost all of KTP andKK are printed in accordance with the applicants’ identity. Viewing from theexisting facilities, applicants satisfy with the supporting facilities available inthe office in general, however, they said that they did mot satisfy withcleanliness of the toilets and parking areas. Custumors were also complaintdue to the absence of saperated area between the parking area foremployees and for the customers. Dealing with the competency of theemployees, the applicants of KTP and KK said that the employee found tobe qualified in doing their tasks and they were also responsive to thecustomers’ compalaint.Keywords: public services quality of public service, Recidential Identity Card, FamilyCard, procedure, time completion.